Casos y cosas: semanario popular (Vol. 2, No. 56) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: El pueblo, sin derecho a la vida?, Al oído, Apuntes al vuelo, La gallina fiósofa, Correo de brujas, Correo franco y con...tranqueza, De carne y hueso, Asalto en poblado, Lo que piensa Fray Candil, Lea ud.

ENGLISH: The people, without the right to life, to the ear, notes on the fly, the philosopher hen, witches' mail, frank mail and with...tranquillity, of flesh and blood, assault in a village, what Fray Candil thinks, Read it yourself.
Cases and things: popular weekly (Vol. 2, No. 56)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas